Farmacovigilância em Fitoterapia: comércio e controle de qualidade de produtos vegetais adquiridos em estabelecimentos farmacêuticos no município de São Luís, estado do Maranhão - Gonçalves, Marcelo de Carvalho (2016)
For most of the population, the difficult access to health services and the trend to use natural products in recovery and preservation of well-being have led to a rise in plants consumption as well as their derivatives as a therapeutic resource, which is very dangerous, considering the risks associated with inadequate conditions of trade and the quality of these products. For this, the present study has evaluated marketing conditions and the quality of some natural products found in private pharmacies and drugstores in São Luís, Maranhão; aiming to contribute to the actions of Pharmacovigilance in Phytotherapy. Based on data available by the Regional Pharmacy Council of the State of Maranhão, through random stratified samples, 15 drug stores and 17 pharmacies were selected to have market conditions investigated by having semi-structured interviews applied to pharmacists, pharmacy owners or assistants pharmacies or drugstores. Camellia sinensis (L.) Kuntze (green tea), Maytenus ilicifolia Mart. ex Reissek (espinheira-santa), Rhamnus purshiana DC. (sacred bark), Cynara scolymus L. (artichoke) and Matricaria recutita L. (chamomile) were identified as the most traded species so samples were acquired for integrity and purity analysis. As a result, it has been possible to observe inadequate marketing conditions, mainly serious health violations, in every selected pharmaceutical establishment. The purity and integrity analysis of commercial samples of green tea and chamomile have identified poor quality, confirming the presence of improper material. Moreover, no evidence of analytical markers or assets defined in specific literature were found. Thus, the results allow evidencing the need for increased surveillance, monitoring and quality control of plant material for medicinal purposes available for sale.